Neuropathogenicity of Two Saffold Virus Type 3 Isolates in Mouse Models - Kotani, Osamu; Naeem, Asif; Suzuki, Tadaki; Iwata-Yoshikawa, Naoko; Sato, Yuko; Nakajima, Noriko; Hosomi, Takushi; Tsukagoshi, Hiroyuki; Kozawa, Kunihisa; Hasegawa, Hideki; Taguchi, Fumihiro; Shimizu, Hiroyuki; et al. (PloS one, 2016)
Saffold virus (SAFV), a picornavirus, is occasionally detected in children with acute flaccid paralysis, meningitis, and cerebellitis; however, the neuropathogenicity of SAFV remains undetermined. The virulence of two clinical isolates of SAFV type 3 (SAFV-3) obtained from a patient with aseptic meningitis (AM strain) and acute upper respiratory inflammation (UR strain) was analyzed in neonatal and young mice utilizing virological, pathological, and immunological methods. The polyproteins of the strains differed in eight amino acids. Both clinical isolates were infective, exhibited neurotropism, and were mildly neurovirulent in neonatal ddY mice. Both strains pathologically infected neural progenitor cells and glial cells, but not large neurons, with the UR strain also infecting epithelial cells. UR infection resulted in longer inflammation in the brain and spinal cord because of demyelination, while the AM strain showed more infectivity in the cerebellum in neonatal ddY mice. Additionally, young BALB/c mice seroconverted following mucosal inoculation with the UR, but not the AM, strain. Both SAFV-3 isolates had neurotropism and mild neurovirulence but showed different cell tropisms in both neonatal and young mouse models. This animal model has the potential to recapitulate the potential neuropathogenicity of SAFV-3.